Influence of compositions containing protein on organoleptic properties of cooked sausages - Fursik, Oksana (My University, 2017)
The influence of composition containing protein based on different protein preparations on the organoleptic properties of cooked sausages is analyzed based on qualimetric analysis. The overall assessment of organoleptic parameters made it possible to state the benefits of experimental formulations using 20% and 30% hydrated composition containing protein over the control sample.
Keywords: білоквмісна композиція; варена ковбаса; якісний аналіз; qualitative analysis; кафедра технології м’яса і м’ясних продуктів